Excursions in Harmonic Analysis, Volume 2 2012
DOI: 10.1007/978-0-8176-8379-5_15
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Inequalities and Dyadic Harmonic Analysis

Abstract: We survey the recent solution of the so-called A 2 conjecture, all Calderón-Zygmund singular integral operators are bounded on L 2 (w) with a bound that depends linearly on the A 2 characteristic of the weight w, as well as corresponding results for commutators. We highlight the interplay of dyadic harmonic analysis in the solution of the A 2 conjecture, especially Hytönen's representation theorem for Calderón-Zygmund singular integral operators in terms of Haar shift operators. We describe Chung's dyadic proo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Indeed, it suffices if the statement of [5,Claim 1.13] holds for a subsequence {n i } i≥1 . This is clear from the proof of [5, Theorem 1.12] (see, [5, Page 272, Line [19][20][21][22]). In Proposition 2.1, we have shown that the ratio Om(p,q) p m−1 stabilizes for m sufficiently large (which is n in [5], which is stronger than necessary.…”
Section: The Number Theory Partmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, it suffices if the statement of [5,Claim 1.13] holds for a subsequence {n i } i≥1 . This is clear from the proof of [5, Theorem 1.12] (see, [5, Page 272, Line [19][20][21][22]). In Proposition 2.1, we have shown that the ratio Om(p,q) p m−1 stabilizes for m sufficiently large (which is n in [5], which is stronger than necessary.…”
Section: The Number Theory Partmentioning
confidence: 92%
“…The study of these weights has been extensive, more information and some recent applications can be found in [9], [21], [22], [19], [14], [15], [4] among many others. There is also interesting complimentary work done in [7].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures and weight and function classes are frequent tools used in harmonic analysis and its applications (such as in [3], [8], [9], to name a few). The study of intersection properties of different classes of these objects is delicate, but results greatly increase our understanding of how these classes interact, uncovering their underlying structure (see [6], [7], [10]).…”
Section: Introductionmentioning
confidence: 99%
“…and reverse Hölder weights are all automatically doubling, and the doubling property is the key point of the definition of spaces of homogeneous type. For more background and applications of doubling measures (particularly from a more modern perspective), see, for example [4], [5], [7], [9], [10], [11], [12], [13]. In particular, dyadic doubling measures have been central to a rich area of study, see, for example [6].…”
Section: Introductionmentioning
confidence: 99%